Preventing chronic diseases : a vital investment (WHO GenevaCH, 2005)
Shows that the impact of chronic diseases in many low and middle income countries is steadily growing. Suggests that it is vital that the increasing importance of chronic diseases is anticipated, understood and acted upon urgentlly. Identifies the problem, suggests the solution and indicates the goal.
Keywords: CHRONIC DISEASES